2009
DOI: 10.1590/s1519-566x2009000500002
|View full text |Cite
|
Sign up to set email alerts
|

Escolha de parceiro para acasalamento em Ceratitis capitata (Wiedemann) (Diptera: Tephritidae): influência do envelhecimento dos machos no sucesso de cópula

Abstract: -The objective of this study was to evaluate the effect of male ageing on male pheromone release and mating success of Ceratitis capitata (Wiedemann). The effects of male ageing on mating were evaluated on fi ve and 21 d-old males by assessing their mating success (males chosen by a female for copulation) and the amount of males releasing the sex pheromone. The mating success was evaluated by using several ratios of young to older males by increasing the number of older males:young males from 1:1 to 5:1. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
(56 reference statements)
1
11
0
1
Order By: Relevance
“…Thus, the hypothesis that females prefer older males despite their reduced fertilization success or viability of their offspring (JONES 2000, JONES & ELGAR 2004 does not seem to apply to C. capitata, at least when there is a choice between young and old males. The data obtained by us is in agreement with other recent studies on different populations of C. capitata (SILVA-NETO et al 2009, SHELLY et al 2011, PAPANASTASIOU et al 2011. Working with the same population used in this study, ANJOS-DUARTE et al (2011b) had found that females did not distinguish between males of 4 and 12 days of age and accepted to mate equally with both; however, they preferred four or 12 days-old males than 20 days-old ones.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, the hypothesis that females prefer older males despite their reduced fertilization success or viability of their offspring (JONES 2000, JONES & ELGAR 2004 does not seem to apply to C. capitata, at least when there is a choice between young and old males. The data obtained by us is in agreement with other recent studies on different populations of C. capitata (SILVA-NETO et al 2009, SHELLY et al 2011, PAPANASTASIOU et al 2011. Working with the same population used in this study, ANJOS-DUARTE et al (2011b) had found that females did not distinguish between males of 4 and 12 days of age and accepted to mate equally with both; however, they preferred four or 12 days-old males than 20 days-old ones.…”
Section: Discussionsupporting
confidence: 92%
“…In each experiment, behavioral observations were performed in the morning for a period of 3 hours (starting time 08:00), quantifying copulations and identifying the mated males. After the removal of the copulating pair, a male of the opposite group was also removed from the cage to maintain equal proportions of males from the different categories inside the cage during the experiment (SILVA-NETO et al 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of non-calling males is not fully understood yet and may be caused by male – male aggression or by genetic factors (Shelly, 2000). It appears that age and time of the day can also affect the emission of pheromone (Flath et al, 1993; Papadopoulos et al, 1998; Papadopoulos et al, 2004; Zhang et al, 2006; Neto et al, 2009). It is known that frequently calling males usually achieve higher mating success (Shelly, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, older males might be inferior to younger ones because of the energetic trade off between longevity and mating success, the accumulation of deleterious germ-line mutations, and the poorer adaptation to current conditions (Cordts and Partridge, 1996; Gosling et al, 2000). Most empirical studies on the effects of age on male mating performance have tested a narrow range of ages (testing relatively young ages) (Shelly et al, 2007; Neto et al, 2009; Perez-Staples et al, 2010), leaving unclear many aspects of the mating behaviour of old ages. To achieve matings, in lekking mating systems, older males should be capable of performing the full repertoire of sexual behaviour and also to compete against younger, more vigorous ones.…”
Section: Introductionmentioning
confidence: 99%